Impact of exercise footwear features on middle-aged and older adults' lower limb muscle activity during gait - Monoharan, Vivek (2019)
Muscle health has been established to decline as a function of age. Owing to this age-related deterioration, it has been noted that older adults (65+ years) exhibit less muscle force production capability during gait, different compensatory mechanisms and co-activation patterns in the lower extremity muscles than young adults. It was noted that studies designed to understand age-related gait muscle activity differences have primarily included subjects of young (20 – 30 years) and older adults (65+ years) but have failed to consider the middle-age (40 – 60 years) group, though muscle strength has been reported to peak and weaken from the fourth decade of life. Footwear features have been noted to positively affect leg muscle activity patterns during gait, thus could be potentially considered as an intervention to improve muscle health in older adults. In the previous studies that advocate footwear’s efficacy in improving lower extremity muscle tone, it was noted the subjects were primarily the younger age group. Inconsistency was also noted in the experimental protocol and data comparison methodology. Surface electromyography (SEMG) is frequently used to study the effect of footwear features on muscles. However, SEMG signal can be affected by a myriad of factors including placement of electrodes, muscle quality, etc. Considering the highly variable nature of SEMG signals and other inter-subject. variability, the normal practice used to average SEMG signals require further evaluation. The objective of the project is to identify exercise footwear features that improve lower extremity gait muscle activity in middle-aged and older adults through amplitude and integrated surface electromyography method. Studies were conducted on fifteen subjects’ dominant leg, five from each agegroup: young (20 – 30 years), middle-aged (40 – 60 years) and older adults (65+ years). Ten lower-extremity muscles were measured along five different phases of a gait cycle on multiple density (FitFlop™), rocker bottom (MBT™), and barefoot (Adidas Adipure Trainer™) footwear against a normal flat-soled canvas footwear as control (North Star™) using multi-channel SEMG system. In summary, it was noted that older subjects when compared with younger and middle age control group exhibited lesser activity in the amplitude and integrated EMG (IEMG) scale on perenus longus and tibialis anterior muscle groups. Intersubject findings showed that MBT™ rocker bottom shoe had a greater effect on older adults than other age groups. FitFlop™ multiple density type did not significantly differ on all the observed age groups. Among the footwear types compared, Adidas Adipure Trainer™ minimalist-type exhibited the most significant difference in all age groups. Based on intra-subject integrated EMG (IEMG) comparison, popular midsole and outsole features have a localized effect only on major calf and shin muscles, but not on other key lower-extremity gait muscles. The study highlighted existence of significant differences in results obtained by various SEMG comparison methods. Additive manufacturing methods for faster prototyping of footwear designs were also highlighted